Revitalising organisations’ emergency succession planning in the face of the Covid-19 outbreak - Bano, Yasmeen; Omar, Siti Sarah; Ismail, Fadillah (European Publisher, 2021)
The purpose of this study is to provide an overview of the need for emergency succession planning during the current covid-19 pandemic. Today, organizations cannot ignore the fact that their employees are their most valuable capital. The pandemic has spread like wildfire with serious consequences on multiple sectors, with most experts postulating that the world is facing the worst recession ever experienced. This pandemic has seriously impacted all businesses, with some permanently shut down like food and beverage, hotels and airlines leaving millions of people jobless on temporary or permanent layoffs. Some, on the other hand, are benefiting from this grim situation such as healthcare products like mask and glove manufacturing, and remote-conferencing services such as Zoom. In this situation, organizations must focus on key changes that can sustain business continuity. This pandemic has forced all organizations to relook and revitalise their emergency succession plan. This study is a review paper which will highlight the difference between long-term and emergency succession planning, the major challenges faced by all organizations and, suggests best options for preparing emergency succession planning during the pandemic crises. This study applies to all sectors of business.